2021
DOI: 10.35848/1347-4065/abec8e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of leaky surface acoustic waves on quartz thin plates bonded to similar-material substrate

Abstract: The propagation and resonance properties of a leaky surface acoustic wave (LSAW) on quartz thin plates bonded to a similar-material substrate are investigated theoretically. The electromechanical coupling factor K 2 on Z-cut quartz (Z–Q) thin plates bonded to an AT-cut 0°X-propagating quartz (AT0°X-Q) support substrate is calculated to be 0.43%, which is approximately three times larger than the maximum value of a single quartz substrate. A positive temperature coefficient of frequency for LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A perfect matching layer (PML) was provided at the bottom of the substrate. 35,36) The mechanical loss Q m and dielectric loss were not taken into consideration. The ScAlN film thickness was set to the film thickness at which K 2 was maximized in the theoretical analysis shown in Table I.…”
Section: Fem Analysismentioning
confidence: 99%
“…A perfect matching layer (PML) was provided at the bottom of the substrate. 35,36) The mechanical loss Q m and dielectric loss were not taken into consideration. The ScAlN film thickness was set to the film thickness at which K 2 was maximized in the theoretical analysis shown in Table I.…”
Section: Fem Analysismentioning
confidence: 99%
“…22) We also theoretically found that the resonance properties of LSAWs on similar-material bonded substrates consisting of a Qz thin plate and a Qz support substrate with different Euler angles are larger than those on a single substrate. 23) We theoretically investigated the propagation and resonance properties of LLSAWs on bonded structures comprising a Qz thin plate and a Qz support substrate, and found the conditions optimal for obtaining small attenuation and large resonance properties. 24) In this study, those properties were investigated in more detail using an analytical solution and a finite element method (FEM).…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a ball surface acoustic wave (SAW) sensor, [9][10][11] as an application of piezoelectric devices [12][13][14][15] such as a planar SAW sensor 16) and quartz crystal microbalances. 17,18) Using the ball SAW sensor as a detector, we developed a portable ball SAW GC.…”
Section: Introductionmentioning
confidence: 99%